O uczniowskim doświadczaniu wsparcia w nowych obszarach poradnictwa = On students` experience of support in new counseling areas - Siarkiewicz, Elżbieta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The family, traditionally ascribed the task of introducing young people into social life, supporting them in difficult or crisis situations, is presently perceived as helpless in relation to unclear, incomprehensible present and unpredictable future. In the article, the author shows some new areas in which youngsters seek help and support. Community websites and students` blogs are presented as the space in which counseling practice is initiated and realized. It is informal, incidental, often anonymous, noncommittal and available to young people at their "beck and call".
Keywords: poradnictwo; media społecznościowe; social media; młodzież szkolna